The Effect of Internal Conflicts, Incentive Bonuses and Safety Riding on Job Satisfaction on The Performance of Shopeefood Drivers In Malang City - Febrian Dimas J. Wibowo; Ida Aju Brahma Sari; Ida Aju Brahma Ratih (Journal of Social Research, 2025)
This study examines the factors affecting the performance and job satisfaction of ShopeeFood drivers in Malang City, Indonesia, in the context of the rapid growth of Shopee's marketplace. The research focuses on several variables, including internal conflicts, incentive bonuses, safety riding, and job satisfaction. The results reveal that internal conflicts significantly affect driver performance (P value = 0.012) but do not significantly impact job satisfaction (P value = 0.327). Incentive bonuses have a significant positive effect on both driver performance (P value = 0.018) and job satisfaction (P value = 0.020). Safety riding is also found to significantly impact both performance (P value = 0.024) and job satisfaction (P value = 0.027). Furthermore, job satisfaction significantly affects driver performance (P value = 0.03). The findings suggest that while incentive bonuses and safety measures are crucial for improving both performance and satisfaction, internal conflicts play a more complex role. This research provides valuable insights for ShopeeFood and similar companies in optimizing driver performance by addressing internal conflicts and reinforcing safety measures, as well as enhancing incentive schemes to improve both job satisfaction and operational efficiency.